Biological function of long noncoding RNA in HER2-positive breast cancer cells - Jeeyeon Lee; Ho Yong Park; Wan Wook Kim; Soo Jung Lee; Jae-Hwan Jeong; Seung Hee Kang; Jin Hyang Jung; Yee Soo Chae (Tumor Biology, 2017)
Purpose: Long noncoding RNA, snaR (small NF90-associated RNA), has been reported to be upregulated in various cancer cell lines. We evaluated the additional role of snaR in HER2-positive breast cancer cell lines. Methods: We explored changes of expression of snaR among the selected long noncoding RNAs which have a potential in cancer proliferation or progression. The proliferation, migration, and invasion of HER2-positive breast cancer cells (SK-BR3) were evaluated by snaR with RNA interruption in 3-(4,5-dimethylthiazol-2yl)-2,5-diphenyltetrazolium bromide, wound-healing assay, and Transwell assay. Results: The expression of snaR was remarkably upregulated in SK-BR3 cell lines together with ANRIL, while the SFMBT2 was downregulated in SK-BR3 cell lines. Although Nespas, 7SK, PSF inhibiting RNA, mascRNA, Hoxa11as, NRON, AK023948, MER11C, p53 mRNA, CAR Intergenic 10, HUC 1 and 2, ZFAS1, SCA8, and SNHG5 were also upregulated and UCA1 was downregulated, the differences were not dominent. Based on the expression result, we explored the functional role of snaR in HER2-positive breast cancer. Downregulation of snaR with small interfering RNA was identified to significanlty inhibit migration as well as proliferation of SK-BR3 cells. Conclusion: In this study, snaR was identified as upregulated and to play a role in cancer progression of HER2-positive breast cancer cells. These results suggest snaR as a potential biomarker for HER2-positive breast cancer.